Antônio Palocci e a retórica da ruptura - o mercado na linguagem do partido dos trabalhadores - Barbosa, Luis Guilherme Camfield (2015)
The hereinafter presented thesis has had as researching goal the political language built by former minister Antônio Palocci throughout the period of his term as Finance minister. Through textual analysis of his speeches, articles and official interviews, a deep thinking has been given on the changes taking place in the Workers Party in its migration from being an opposing party into government after 2002 presidential elections especially regarding subjects of economic policies. For such, it will be revisited a historical debate between developmentalism and liberalism in the Brazilian context, as well as a brief resumption of the establishment and trajectory of the Workers Party. The objective of such chain of topics is to list the necessary tools for the conceptual examination of the language of the former minister.